Infrastructure and promotion: critical factors in the weak positioning of Magical Towns in Ecuador: case studies of Cotacachi, El Chaco, and Agua Blanca - Farinango Cabezas , Luis (2025)
The Pueblos Mágicos project in Ecuador aims to develop and highlight the natural and tourist attractions of various towns and their territories. Since its implementation in Ecuador, different studies have sought to evaluate the impact and significance of the project. This article aims to recognize the positioning of three Pueblos Mágicos through work on marketing variables. In this context, the objective of this article is to analyze the positioning of the Pueblos Mágicos of Cotacachi, El Chaco, and Agua Blanca. To achieve this goal, a mixed methodology was used, employing data collection tools such as semi-structured interviews with municipal officials and surveys of residents and visitors. One of the most relevant conclusions is that the Pueblos Mágicos project has led to urban development but not rural development.